Early-stage responses to Plasmodiophora brassicae at the transcriptome and metabolome levels in clubroot resistant and susceptible oilseed Brassica napus. (16th November 2022) - Adhikary, Dinesh; Kisiala, Anna; Sarkar, Ananya; Basu, Urmila; Rahman, Habibur; Emery, Neil; Kav, Nat N. V.
Abstract : Primary metabolites and genes corresponding to important metabolic pathways that may be potentially involved in mediating resistance to clubroot disease in canola were identified. Arrows indicate increase in metabolite levels and gene expression. Abstract : Clubroot, a devastating soil-borne root disease, in Brassicaceae is caused by Plasmodiophora brassicae Woronin ( P. brassicae W.), an obligate biotrophic protist. Plant growth and development, as well as seed yield of Brassica crops, are severely affected due to this disease. Several reports described the molecular responses of B. napus to P. brassicae ; however, information on the early stages of pathogenesis is limited. In this study, we have used transcriptomics and metabolomics to characterize P. brassicae pathogenesis at 1-, 4-, and 7-days post-inoculation (DPI) in clubroot resistant (CR) and susceptible (CS) doubled-haploid (DH) canola lines. When we compared between inoculated and uninoculated groups, a total of 214 and 324 putative genes exhibited differential expression ( q -value < 0.05) at one or more time-points in the CR and CS genotypes, respectively. When the inoculated CR and inoculated CS genotypes were compared, 4765 DEGs were differentially expressed ( q -value < 0.05) at one or more time-points. Several metabolites related to organic acids ( e.g., citrate, pyruvate), amino acids ( e.g., proline, aspartate), sugars, and mannitol, were differentially accumulated in roots in response to pathogen infection when the CR and CS genotypes were compared. Several DEGs also corresponded to differentially accumulated metabolites, including pyrroline-5-carboxylate reductase (BnaC04g11450D), citrate synthase (BnaC02g39080D), and pyruvate kinase (BnaC04g23180D) as detected by transcriptome analysis. Our results suggest important roles for these genes in mediating resistance to clubroot disease. To our knowledge, this is the first report of an integrated transcriptome and metabolome analysis aimed at characterizing the molecular basis of resistance to clubroot in canola.